BIMBINGAN PENYULUHAN TERHADAP PEMAHAMAN ORANG TUADALAM MENCEGAH STUNTING PADA ANAK USIA DINI - Nihwan Nihwan (Jurnal Bimbingan Penyuluhan Islam, 2019)
Stunting is a condition of malnutrition status that is chronic in the period of growth and development since the beginning of life. One effort in the prevention of Stunting in early childhood is through increasing knowledge, attitudes and behavior about nutritional counseling. Therefore, to prevent stunting in children, mothers need to consume proper nutrition, especially during pregnancy until the child is born and is 18 months old. Parents' knowledge about nutritional health and food support for child nutrition needs to be conducted by conducting counseling, counseling, parenting programs and maximizing posyandu. With this kind of activity, of course parents will pay more attention to health and nutritional needs for children in the golden age of their development.Understanding of balanced nutrition in early childhood is also a trigger to prevent Stunting, so parents are able to understand food and nutrition needs for children according to their developmental stages. By doing guidance and counseling effectively in understanding Stunting problems in children, parents will pay more attention to Nutrition and Nutrition in early childhood.